Managing Competing Interests: A Review of Ethics in Military Procurement. (12th September 2017) - King, David R.; Sekerka, Leslie E.
Abstract : Conflicts of interest represent an increasing problem in organizations, given the expansion of stakeholder concerns, needs, and expectations. Existing remedies to address these conflicts largely involve aligning management incentives with the interests of investors, or recusing parties with special interests from the decision-making effort. Both focus on a dyad between the primary stakeholder and the decision-maker. However, increasingly complex situations involving multiple stakeholders exist. The added complexity of considering multiple stakeholders heightens uncertainty that can facilitate the pursuit of self-interest. Ironically, a potential remedy may involve ensuring the presence of competing interests. A review of military procurement suggests that competing interests can mitigate self-interest.